Inhibition of monoacylglycerol lipase restrains proliferation, migration, invasion, tumor growth and induces apoptosis in cervical cancer. Issue 2 (7th December 2021) - Wang, Chao; Li, Zhoulei; Zhong, Linlin; Chen, Youguo
Abstract: Aim: Cervical cancer is one of common diseases among women. There are limited therapies for patients with metastatic or recurrent cervical cancer. This study sought to explore the role of monoacylglycerol lipase (MAGL), an important metabolic enzyme, in cervical cancer progression. Methods: In in vitro experiments, MAGL expression was inhibited by si‐MAGL or JZL184 in cervical cancer cells. Quantitative real‐time polymerase chain reaction and western blotting were performed to measure the expression of target molecules. Proliferation of cervical cancer cells was assessed by CCK‐8 and colony formation assays. Apoptosis and cell cycle progression were evaluated by flow cytometry. The migration and invasion were detected by transwell assay. The in vivo tumor growth was detected in nude mice. TUNEL was utilized to observe apoptotic cells in tumor tissues. Results: MAGL was upregulated in cervical cancer tissues and cells. Further, MAGL inhibition suppressed the growth of cervical cancer cells in vitro and in vivo. In addition, apoptosis and G1‐phase cell cycle arrest were induced by MAGL knockdown. MAGL silencing‐mediated upregulation of Bax and cleaved caspase‐3, and downregulation of Bcl‐2 was responsible for triggering apoptosis. More importantly, the migration and invasion of cervical cancer cells were restrained by MAGL depletion. Conclusions: MAGL drives the progression of cervical cancer, which can be a promising candidate to identify effective therapy for cervical cancer.